2019
DOI: 10.1088/1755-1315/365/1/012065
|View full text |Cite
|
Sign up to set email alerts
|

Model of surface runoff estimation on oil palm plantation with or without biopore infiltration hole using SCS-CN and ANN methods

Abstract: Surface runoff by rainfall on oil palm-cultivated land can cause erosion. Method conservation of making biopore infiltration hole on sloping oil palm plantations land has been shown to reduce this runoff. It has been experimentally proven in plots with or without biopores. However, the estimation model of the surface runoff event has not been studied comprehensively. The main novelty of this work is using surface runoff and rainfall observation directly database on oil palm land for the predicted runoff. Estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Yanwei [22] describes the average values for Well diameters and Space between the good power function indicators are 2.6 and 2.5, respectively, indicating that there is little difference between them, which is related to the infiltration volume reduction. Meanwhile, Devianti's research presents results indicating that the total volume of surface discharge can be reduced by 26.50% in experimental plots with infiltration holes in the same diameters and depth [23]. Furthermore, Zhangs [24] demonstrated that the infiltration holes at various depths boosted daily soil evaporation for the first 26 days under the high starting soil water content, thereafter it declined.…”
Section: Discharge Output From Sweep/wmentioning
confidence: 96%
“…Yanwei [22] describes the average values for Well diameters and Space between the good power function indicators are 2.6 and 2.5, respectively, indicating that there is little difference between them, which is related to the infiltration volume reduction. Meanwhile, Devianti's research presents results indicating that the total volume of surface discharge can be reduced by 26.50% in experimental plots with infiltration holes in the same diameters and depth [23]. Furthermore, Zhangs [24] demonstrated that the infiltration holes at various depths boosted daily soil evaporation for the first 26 days under the high starting soil water content, thereafter it declined.…”
Section: Discharge Output From Sweep/wmentioning
confidence: 96%
“…High rates of runoff generation can be mitigated by implementing water retention managing strategies (e.g. frond piles, silt pits, biopores, planting understory vegetation) (Tarigan et al 2016, Wawan et al 2019, Devianti et al 2020, as well as preserving riparian zones to control stream properties (Luke et al 2017, Chellaiah and Yule 2018a, 2018b, Merten et al 2020. These studies are motivated by the trends in runoff regeneration, and soil erosion, and soil, when oil palm replaces forests.…”
Section: Fluvial Processesmentioning
confidence: 99%
“…The water storage system in the soil bio pure allows oil palm plantation areas to effectively control flooding when it rains and avoid drought when rainfall decreases. In addition, compared to other crops, oil palm is relatively water efficient (not wasteful of water) while producing bioenergy (37).…”
Section: Stakeholder Perceptions In the Existing Condition Of Oil Pal...mentioning
confidence: 99%